Security and Attitudes Toward Globalization: A Multilevel Analysis - James E. Cameron; Lucie Kocum; John W. Berry (Journal of Social and Political Psychology, 2020)
Globalization implicates a number of social psychological processes and outcomes, including openness to ideas, products, and people from outside one’s national boundaries. Drawing from theory and research on intergroup threat, the researchers posited that people will be more open to connections between their nation and others if they feel their economic situation and culture are relatively secure. They found some support for these hypotheses in 2 sets of archival survey responses collected by the Pew Global Attitudes Project in 2002 (40 countries; N = 34,073) and 2009 (25 countries; N = 22,500). Personal economic security and perceived national economic security were associated with more positive attitudes toward globalization in both survey years. However, country-level variables—development status (as indexed by the United Nations’ Human Development Index) and aggregated economic and cultural security—moderated the individual-level effects in several ways. Individual perceptions of national economic security more strongly predicted attitudes toward globalization in more favourable climates (e.g., in more developed countries, and at higher levels of country-level national economic security). Individual-level cultural security was positively associated with attitudes toward globalization in countries with higher levels of socioeconomic development, but negatively related to those attitudes in less developed nations. The results provide some new perspectives on individual and collective factors that inform the perceived benefits of globalization.